Experimental Study on the Evolution Mechanism of Landslide with Retaining Wall Locked Segment - Han-Dong Liu; Jia-Xing Chen; Zhi-Fei Guo; Dong-Dong Li; Ya-Feng Zhang (Geofluids)
The failure of locked segment-type slopes is often affected by rainfall, earthquake, and other external loads. Rainfall scours the slope and weakens the mechanical properties of rock-soil mass. At the same time, rainfall infiltrates into cracks of slope rock mass. Under the action of in situ stress, hydraulic fracturing leads to the development and expansion of rock cracks, which increases the risk of slope instability. Under seismic force, the slope will be subjected to large horizontal inertial force, resulting in slope instability. In this paper, a self-developed loading device was used to simulate the external loads such as rainfall and earthquake, and the model tests are carried out to study the evolution mechanism of landslide with retaining wall locked segment. Three-dimensional laser scanner, microearth pressure sensors, and high-definition camera are applied for the high-precision monitoring of slope shape, deformation, and stress. Test results show that the retaining wall locked segment has an important control effect on landslide stability. The characteristics of deformation evolution and stress response of landslide with retaining wall locked segment are analyzed and studied by changing the slope shape, earth pressure, and the displacement cloud map. The evolutionary process of landslide with retaining wall locked segment is summarized. Experimental results reveal that as the landslide with retaining wall locked segment is at failure, the upper part of the landslide thrusts and slides and the retaining wall produces a locking effect; the middle part extrudes and uplifts, which is accompanied with shallow sliding; and compression-shear fracture of the locked segment leads to the landslide failure.